An Experimental Study on the Effect of Liquid Concentration on the Atomization Performance of Low-pressure Atomizing Nozzles. Issue 1 (1st December 2022) - Lei, Han; Li, Ge; Wang, Fei; Chen, Tiejun; Ten, Li; Ding, Yong
Abstract : in order to study the phenomenon and mechanism of paint low-pressure atomization spraying and improve the spraying technology, the effect of liquid concentration on the atomization performance of low-pressure atomizer was studied. In this paper, an experimental platform for measuring the spraying of low-pressure atomizing nozzle was built. Mixing the same paint with clean water to obtain liquids of three different concentrations and using them as the mediums respectively, the flow, the atomization angle and the atomization characteristics of low-pressure fine atomizing nozzle with aperture of 0.33mm under the pressure of 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa and 0.8MPa were studied. The measured experimental data show that there is a positive correlation between the flow of atomizer and atomization pressure, and the larger the liquid concentration is, the smaller the flow is; The variation trend of atomization angle with the increase of pressure is related to the liquid concentration and is stable between 45 ° and 60 °; The average droplet size of atomized droplets has a negative correlation with atomization pressure, and the higher the liquid concentration, the larger the average droplet size. The experimental results show that the liquid concentration has a significant impact on the atomization performance of low-pressure atomizer, and the measured data are helpful for the application of paint spraying under low-pressure conditions.